Reliability and validity of the short quality of life scale among bank employees in Guangxi, China - Huang, Qianwei; Mo, Qiqing; He, Huiming; Bai, Xinyu; Zhang, Jie; Ma, Zhenyu; Chen, Guoxiang (Frontiers in Psychology, 2025)
BackgroundThis study aims to assess the reliability and validity of the Quality of Life Scale (QOLS-6) among bank employees in Guangxi, grounding the investigation in the theoretical framework of quality of life measurement and psychological well-being. Given the increasing importance of mental health in the workplace, understanding how psychological conditions impact life quality is critical. The QOLS-6, a widely used tool for measuring quality of life, has been shown to have potential for application in diverse populations.MethodsA cluster sampling method was used in the study. A questionnaire survey was conducted among 3,974 employees of a bank in Guangxi Province of China. To evaluate its performance across different mental health conditions, 298 participants in the suicidal ideation group and 3,676 in the non-suicidal ideation group. The non-suicidal group was randomly divided into two subsamples, with subsample A (n = 1,838) for exploratory factor analysis (EFA) and subsample B (n = 1,838) for confirmatory factor analysis (CFA). Reliability and validity were assessed for each group, enhancing the understanding of QOLS-6’s sensitivity and effectiveness in capturing quality of life variations across different psychological profiles. Cronbach’s α coefficient was used to analyze the internal consistency reliability. EFA and CFA were used to examine the construct validity. Spearman correlations was used to evaluate the concurrent validity.ResultsThe QOLS-6 demonstrated good internal consistency, with Cronbach’s α values of 0.908 and 0.857 for the two groups, respectively, and 0.865 for the overall sample. Its construct validity was supported by high KMO values of 0.841, 0.805 and 0.818 for the suicidal ideation group, subsample A and total sample, respectively. Exploratory factor analysis of the QOLS-6 revealed a single-factor structure. However, confirmatory factor analysis demonstrated that a three-factor model provided a better fit. The QOLS-6 showed negative correlations with depression, loneliness, hopelessness, and job burnout while positively correlating with job satisfaction and family function.ConclusionThe QOLS-6 has demonstrated strong reliability and validity among bank employees in Guangxi, China. While exploratory factor analysis suggested a one-factor structure, confirmatory factor analysis supported a three-factor model, indicating a multidimensional nature. Based on the theoretical framework of quality of life and the design of the scale’s content, the three-factor model demonstrates statistical and theoretical validity. Additionally, the scale exhibited significant correlations with key psychological factors, further supporting its applicability. These findings suggest that the QOLS-6 is an effective tool for assessing quality of life in diverse psychological contexts.